Food for naught: Using the theory of planned behaviour to better understand household food wasting behaviour - Werf, Paul; Seabrook, Jamie A.; Gilliland, Jason A. (The Canadian geographer, 2019)
To better understand food wasting behaviour, the theory of planned behaviour was used to inform the development of a survey which was administered to households in London, Ontario, Canada. Respondent households (n = 1,263) threw out avoidable food waste 4.77 times/week (SD = 4.81, Mdn = 4.0) and 5.89 food portions/week (SD = 5.66, Mdn = 4.0). When asked to choose one of three possible motivators to reduce food wasting behaviour, 58.9% selected reducing monetary loss as their first choice and this was significantly (p < 0.001) higher than both reducing environmental impact (23.9%) and reducing social impacts (17.2%). A linear hierarchical regression analysis (R2 = 0.30, p < 0.001) on intention to avoid food waste demonstrated that perceived behavioural control (p < 0.001) and personal norms (p < 0.001) had the greatest positive impact on intention. A linear hierarchical regression analysis (R2 = 0.32, p < 0.001) on self‐reported food wasting behaviour showed that perceived behavioural control (p < 0.001) and personal attitudes (p < 0.01) resulted in less food wasting behaviour, while more children in a household (p < 0.01) resulted in more food wasting behaviour. Interventions that seek to strengthen perceived behavioural control and convey the monetary impact of food waste could help reduce its disposal. De la nourriture inutile : utiliser la théorie du comportement axé sur un objectif pour mieux comprendre le gaspillage de nourriture au sein des ménages Pour mieux comprendre le phénomène de gaspillage de nourriture, nous avons utilisé la théorie du comportement axé sur un objectif pour concevoir une enquête qui a été réalisée auprès de ménages à London, en Ontario, Canada. Les ménages répondants (n=1,263) jetaient des déchets de cuisine évitables 4.77 fois/semaine (SD = 4.81, Mdn = 4.0) et 5.89 portions de nourriture/semaine (SD = 5.66, Mdn = 4.0). Lorsqu'on leur a demandé de choisir l'un des trois éléments de motivation possibles pour diminuer le gaspillage de nourriture, 58.9% ont choisi l'aspect financier comme premier choix, ce qui était sensiblement (p < 0.001) plus élevé que l'impact environnemental (23.9%) et les impacts sociaux (17.2%). Une analyse linéaire avec régression hiérarchique (R2 = 0.30, p < 0.001) de l'attitude envers le gaspillage de nourriture a démontré que le contrôle comportemental perçu (p < 0.001) et les normes personnelles (p < 0.001) avaient une forte influence. En effet, une analyse linéaire avec régression hiérarchique (R2 = 0.32, p < 0.001) du gaspillage de nourriture déclaré par les répondants a montré que le contrôle comportemental perçu (p < 0.001) et les attitudes personnelles (p < 0.01) entraînaient une diminution du gaspillage de nourriture, alors qu'un plus grand nombre d'enfants dans un ménage (p < 0.01) entraînait une augmentation du gaspillage de nourriture. Conséquemment, les interventions visant à renforcer le contrôle comportemental perçu et à faire connaître les impacts financiers du gaspillage de nourriture pourraient contribuer à la diminution de la quantité de nourriture jetée. Key Messages Respondent households threw out food 4.77 times/week and 5.89 food portions/week. Reducing monetary impact of food waste was identified as the most selected food waste reduction motivator. Perceived behavioural control was identified as an important determinant of food wasting behaviour.